Assessment of the long-term stability of the polymer of intrinsic microporosity PIM-1 for hydrogen storage applications. (1st January 2019) - Rochat, Sébastien; Polak-Kraśna, Katarzyna; Tian, Mi; Mays, Timothy J.; Bowen, Christopher R.; Burrows, Andrew D.
Abstract: Polymers of intrinsic microporosity, such as PIM-1, advantageously combine high surface areas with good processability, which are attractive properties for hydrogen storage applications. Here we address the lack of data on the long-term mechanical stability and hydrogen uptake capacity of PIM-1 in a study carried out over 400 days. Our results show that most mechanical and surface properties of PIM-1 remain stable over this time. In particular, the mechanical strength and elasticity are maintained, and the surface area remains constant over the course of our observations. In contrast, we detected a small but statistically significant decrease of the hydrogen storage capacity of the material over time, particularly in the first stages of aging. We attribute this phenomenon to the slow rearrangement of the polymer scaffold in the solid state. Taken together, our experiments demonstrate that PIM-1 possesses the long-term stability required for realistic applications in hydrogen storage or in gas separation. Highlights: Thin films made of microporous polymer PIM-1 were monitored over 400 days. The mechanical properties (strength and elasticity) are maintained. The surface properties (surface area) remain constant. The hydrogen uptake (up to 10 MPa) slightly decreases over time. The stability of PIM-1 makes it a promising material for long-term hydrogen storage.